Respuesta :
Answer: x = 3.5 and y = -2.5
Step-by-step explanation: The pair of simultaneous equations are given as
3x + y = 8 ———(1)
x - 3y = 11 ———(2)
From equation (2) make x the subject of the equation
x = 11 + 3y
Substitute for the value of x into equation (1)
3(11 + 3y) + y = 8
33 + 9y + y = 8
We collect like terms and we now have
33 - 8 = -10y
25 = -10y
Divide both sides of the equation by -10
-2.5 = y
Having solved for the value of y, we now substitute for y into equation (2)
x - 3y = 11
x - 3(-2.5) = 11
x + 7.5 = 11
x = 11 - 7.5
x = 3.5
Therefore x = 3.5 and y = -2.5
Answer:
X=18.5,Y=-2.5
Step-by-step explanation:
Using substitution method
3x+y=8.........(equation 1)
x-3y=11...…....(equation 2)
Making x in equation 2 has subject of the formula
x=11+3y
Substitute x in equation one
3(11+3y)+y=8
33+10y=8
10y=8-33
10y=-25
y=-25/10
y=-2.5
Substitute y in equation 2
x-3(-2.5)=11
X-7.5=11
x=11+7.5
x=18.5